The Effect of Genre Expectation on EFL Brazilian Students' Inference Generation and Reading Comprehension - Caldart Roscioli, Deise; Braga Tomitch, Lêda Maria (Revista do GEL, 2014)
This study investigated the influence of genre expectation on EFL Brazilian undergraduate students’ inference generation and reading comprehension. Eleven EFL readers from the last semester of the Letras Course at UFSC participated in this study. The effect of genre expectation was investigated by means of the assessment of students’ inference making and reading comprehension in relation to two texts, namely a literary story and a news story. The instruments used for data collection were the Pause Protocol (CAVALCANTI, 1989) in the version adapted by Tomitch (2003) and a set of reading comprehension questions. Participants’ reports from the Pause Protocol were transcribed and their utterances were categorized in accordance with Narvaez, van den Broek and Ruiz’ (1999) Inference Categorization Model. Furthermore, participants’ answers in the reading comprehension questions were analyzed and scored. Results obtained from this research have shown that participants’ inference generation was not significantly influenced by genre expectation. However, data from the Pause Protocol reports and reading comprehension questions provided evidence that text type did influence participants’ reading comprehension. Furthermore, data from participants with outstanding performance on the reading comprehension questions provide evidence that they were controlling their reading strategies considering the genre being read.